MANAGEMENT ACCOUNTING IN THE FORMATION OF DISTRIBUTION COSTS IN RETAIL TRADE - O. Diakonova; O. Andreeva (Вестник университета)
The article considers the essence of management accounting costs in retail organizations. In the market economy, commercial enterprises to achieve efficiency in the production implement a system for managing economic activities. The management accounting system allows to estimate efficiency of production and effectively control costs of the organization.